MENINGKATKAN KEMAMPUAN FISIK MOTORIK KASAR ANAK USIA 4-5 TAHUN MELALUI PERMAINAN TRADISIONAL LOMPAT TALI DI PAUD AT TAQWA - Samsiah, Euis; Ismail Fahmi, Ade; Triyati, Marwah (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Gross motor development in early childhood is very important because it affects basic motor skills, balance, and body coordination. However, initial observations at the At-Taqwa Early Childhood Education Center (POCD) showed that most children aged 4–5 years had difficulty jumping and running, which was caused by a lack of diverse stimulation in the learning process. This condition encourages the need for more interesting learning strategies that are appropriate to the child's developmental stage. One way is with the traditional jump rope game. The purpose of this study was to develop the development of gross motor skills in children aged 4–5 years through the traditional jump rope game at the At-Taqwa Early Childhood Education Center (POCD). This study used the Classroom Action Research (CAR) method with the Kemmis and Taggart model which was carried out in two cycles. The subjects of this study were 11 children, consisting of 7 girls and 4 boys. Data were collected through observation and documentation with success indicators including the ability to jump on two feet in balance, jump 20 cm high, and run in a directed manner. The results showed a significant increase from the pre-cycle to the second cycle. In the pre-cycle, most children were unable to jump and run well, while by the end of the second cycle, 81.18% had achieved the very good development category. These findings demonstrate that the traditional jump rope game is effective in improving gross motor skills in early childhood and can also be used as an alternative educational and fun learning strategy in early childhood education.